Investigating the relationship between colour change and the tensile strength of sandstone from Singapore’s Jurong formation with temperature and rate of temperature change - Soh, Wei Jie (2015)
There are many underground structures like tunnels and caverns built in Singapore. As with any structure, thermal damage caused by fires is a concern. This study aims to find out how the strength of the Jurong Formation sandstone in Singapore’s west varies with increases in temperature. It also aims to find out if the percentage change of the values of the L*a*b* colour parameters varies with increases in temperature. (i.e. find out how much colour change is caused due to increases in temperature) Sandstone specimens of 50mm in diameter and 60mm in diameter undergo colour analysis where the L*a*b* colour values were measured. They were then subjected to 9 combinations of heating conditions with specimens in batches of 4 for each combination. These batches were heated to surface temperatures of 140oC, 170oC and 200oC and exposed to rates of temperature change of the air in the furnace of 20oC/min, 30oC/min and 50oC/min. 10 sandstone specimens were not subject to heating conditions so that they could be compared to the specimens that underwent heating. The L*a*b* colour values of the heated specimens were measured again and compared to the L*a*b* colour values of the specimens before heating. The percentage change of L*a*b* colour values due to heating was calculated from the difference in L*a*b* colour values of the specimens before and after heating. The specimens were then subjected to the Brazilian tensile disc test. Finally, the percentage change in L*a*b* colour values and the Brazilian tensile strength values are compared to the heating conditions the specimens are subjected to. The experiment showed that the specimens that underwent heating experienced negative percentage changes to the b* colour values. No consistent trend was observed of how the percentage changes in b* colour values vary with increases in surface temperature and rate of temperature change of the air in the furnace of the sandstone specimens. However, upon comparison of the averaged percentage change of b* colour values with surface temperature while ignoring the rate of change of temperature in the air of the furnace, it was observed that the percentage change of b* colour values stays around -5.0% for specimens 50mm in diameter and -4.0% for specimens 60mm in diameter for the surface temperatures of 140oC, 170oC and 200oC. Interestingly enough, the sandstone specimens show an increasing trend of Brazilian tensile strength values with increasing surface temperatures. It is recommended that similar future experiments use a higher range of temperatures and more specimens so that clearer trends between colour change and Brazilian tensile strength values with increasing surface temperatures can be established.